I dentify Dotential for use of decision support systems to increase the effectiveness of banking performance " Study in the Islamic banking sector (Journal of Hama University, 2019)
The objective of this study is to assess the role of the potential of decision support systems in increasing the effectiveness of performance in the private banking sector. In reviewing the scientific contributions in this field, the study model was formulated. The study sample consisted of 100 employees working in banking functions related to the banking decision support system, the response rate was 74%. The statistical package SPSS was used in the statistical analysis, and the appropriate statistical methods were used.The analysis and interpretation of the results showed that the potential for using decision support systems (physical, technical, organizational) in the private banking sector (Syria International Islamic Bank - Sham Bank) contribute to increasing the efficiency of performance